2016
DOI: 10.1016/j.jadohealth.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Views of Young People With Chronic Conditions on Transition From Pediatric to Adult Health Services

Abstract: Purpose-This study sought to identify and describe the views of young people with chronic conditions about the transition from pediatric to adult services.Methods-Q methodology was used to identify young people's views on transition. A set of 39 statements about transition was developed from an existing literature review and refined in consultation with local groups of young people. Statements were printed onto cards and a purposive sample of 44 young people with chronic health conditions was recruited, 41 rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
(35 reference statements)
1
29
0
Order By: Relevance
“…However, this transition may be met with resistance from patients and their parents as it can mean leaving multidisciplinary care clinics and instead receiving care from multiple adult specialists, who may not coordinate care or treatment decisions and may not have a specific knowledge or interest in treating SB. 8,[12][13][14][15] One study found that the mean number of specialists seen by an adult with SB was 3.8 and that 71% of adults with SB reported difficulty in accessing medical care. 16 Generally, transitioning to knowledgeable adult providers is appropriate and indicated for chronic childhood onset conditions, and there should be a planned, purposeful move to the new care provider or team.…”
Section: Medical Care Needs Into Adulthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this transition may be met with resistance from patients and their parents as it can mean leaving multidisciplinary care clinics and instead receiving care from multiple adult specialists, who may not coordinate care or treatment decisions and may not have a specific knowledge or interest in treating SB. 8,[12][13][14][15] One study found that the mean number of specialists seen by an adult with SB was 3.8 and that 71% of adults with SB reported difficulty in accessing medical care. 16 Generally, transitioning to knowledgeable adult providers is appropriate and indicated for chronic childhood onset conditions, and there should be a planned, purposeful move to the new care provider or team.…”
Section: Medical Care Needs Into Adulthoodmentioning
confidence: 99%
“…Due to the range in ability levels and support systems among adults with SB, a one-size-fits-all model does not appropriately address all aspects of transitioning care. 14 Resistance to the transition from pediatric to adult care is multifaceted and may come from anyone involved in an individual's care. Transition may be delayed because of anxiety about the change in providers or a lack of initiative due to apathetic feelings regarding such changes.…”
Section: Transition From Adolescent To Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…The hope is that when the pediatrician "officially" ceases being the primary care provider and the adult-focused care begins, the transition will be smooth and successful. [1][2][3] In their review article, Reichek and Danner-Koptik 1 summarize the transition process for childhood cancer survivors in this way: "the broad goal of transition is for the AYAs [adolescents and young adults] to achieve successful engagement in the adult system, to receive developmentally and medically appropriate care, and to facilitate their maximum potential and optimal quality of life. The process should be coordinated, family centered, and planned, so the AYA can mature into the knowledge of the transition to adult care and have supports in place to achieve the transition goal.…”
Section: Transition Of Carementioning
confidence: 99%
“…There is, however, no “one-size fits all model of transition” (2). That approach may indeed be inappropriate, as it may not consider variation in the young people themselves, or their preferred style of engagement (3). Personalized planning for transition seems more appropriate, where young people’s preferences, combined with the knowledge health-care professionals have of their patient population, could lead to more effective and efficient engagement with adult care.…”
Section: Introductionmentioning
confidence: 99%